Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Tentang Dukungan Suami Selama Proses Persalinan Di Bendan Banyudono Boyolali - WARDHANA, Akbar Putra, Dr. Fai zah Betty R.,A.,S.Kep., MKes, Enita Dewi,S.Kep.,Ns.,MN (2016)
The existence of acompanionis needed to assist a mother in child birth guide. The task of acompanionis to give support during pregnancy, labor and child birth, this simplifying the course of child birth. Therefore,a husband who is needed because it can provide support to a mother during child birth. Support can be given by a husband agains this wife motivated physically and psychologically. The support given can make mothers who experience child birth feel safe and comfortable. The aim ofthis study was to determine the effect tof health educationon the knowledge of the husband's support during labor in Bendan, Banyudono. This research is aquantitative research with one group pretest posttes tdesign. Population of this research is the husband who has apregnant wife's first child (primigravida). The total sample of 32 respondents with total sampling technique.The instrument used in this study is a questionnaire that contains knowledge about the husband's support during child birth. Analyze data using a non-parametric Wilcoxon rank test with p value: 0,000<α =0.05. The result is the influence of knowledge before and after being given health education. Advice for respondents to be able to apply the results of health education when accompanying his wife during delivery. Keywords: Suppor thusband, knowledge, health education.